Effects of sampling strategy, geographical origin, and soil on stable isotopes and multi-elements for the traceability of Chinese PGI oranges - Jiahui Wu; Hao Deng; Guang Wu; Hanyi Mei; Karyne M. Rogers; Yurong Huang; Shengzhi Shao; Chunlin Li; Ping Wang; Jing Nie; Yuwei Yuan; Yongzhi Zhang (Food Control, 2026)

Enhancing transferability of foliar trait retrieval models: A comparative analysis of transfer learning strategies and domain shift characterization - Yurong Huang; Nanfeng Liu; Wenqian Chen; Wei Tan; Yujia Deng; Zhihui Wang; Adam Chlus; Jian Shen; Philip A. Townsend (Remote Sensing of Environment, 2026)

Monitoring hydrothermal degradation of CFRP-concrete interfaces using carbon nanotube yarn sensors - Miaochang Zhu; Yurong Qiu; Jun Deng; Chaoqun Zeng; Saeid Mehrpay (Engineering Structures, 2026)

The evolution of phototrophic Fe(II)-oxidizing bacteria shaping the distribution of iron-bound phosphorus in water columns - Shan Huang; Yuanyuan Ren; Chao Peng; Chao Zhong; Jiahao Chen; Yurong Deng; Geng Wu; Yuanyuan Liu; Hailiang Dong; Juan Liu (Chemical Geology, 2026)

Regulatory mechanisms of carboxylic ligands with varying carboxyl group richness in Fe(II)-catalyzed ferrihydrite transformation - Yuefei Ding; Anxu Sheng; Jiahao Chen; Yurong Deng; Xinglan Cui; Juan Liu (Geochimica et Cosmochimica Acta, 2025)

Point discharge molecular emission spectrometer as a highly sensitive GC detector for the analysis of furans in food products - Yuan Yang; Xiaoli Wu; Qiuyi Yan; Hongling Zhou; Yurong Deng; Chengbin Zheng (Food Chemistry, 2025)

Distributional characteristics and causes of single-layer stratiform clouds over typical region in the southeastern Pacific Ocean - Ximing Deng; Yong Han; Chunsong Lu; Xinxin Xie; Yurong Zhang; Tianwei Lu; Li Dong; Qicheng Zhou (Atmospheric Research, 2025)

Stem trichome polarity development in Gossypium hirsutum: insights into GhPRP gene regulation - Huanying Deng; Longen Ma; Li Yu; Yanhao Zhao; Yurong Jiang; Junkang Rong (Plant Cell Reports, 2025)

Black carbon in major global source areas from 2000 to 2023: Spatiotemporal variation, vertical distribution, and extreme case analysis - Yurong Zhang; Yong Han; Yan Liu; Ximing Deng; Tianwei Lu; Qicheng Zhou; Li Dong (Environmental Pollution, 2025)

Regulation of ferrihydrite biotransformation by Fe(II) supply rates and extracellular polymeric substances - Anxu Sheng; Yurong Deng; Yuefei Ding; Linxin Cheng; Yuyan Liu; Xiaoxu Li; Yuji Arai; Juan Liu (Geochimica et Cosmochimica Acta, 2024)

3D printed microplasma optical emission spectrometry coupled with ZIF-8 based dispersive solid-phase extraction for field analysis of waterborne arsenic - Jiahui Yang; Yao Lin; Xi Wang; Yuanyuan Li; Yurong Deng; Chengbin Zheng (Analytica Chimica Acta, 2024)

Spatiotemporal variations and source on black carbon over Chongqing, China: Long-term changes and observational experiments - Yurong Zhang; Yong Han; Li Dong; Ximing Deng; Dan Ye; Shiyong Shao (Science of The Total Environment, 2024)

Deciphering microbial drivers of soil organic matter mineralization in surface and subsurface soil during long-term vegetation succession - Jingwei Shi; Lei Deng; Lin Yang; Yajing Dong; Yang Liao; Jiwei Li; Yurong Liu; Chengjie Ren; Feng Yang; Zhouping Shangguan; Yakov Kuzyakov (Agriculture, Ecosystems & Environment, 2024)

Dielectric barrier discharge-induced chemical vapor generation for highly sensitive analysis of iodine in seawater by ICP-MS - Yuke Wu; Jiahui Yang; Yurong Deng; Jinyi Zhang; Chengbin Zheng (Analytica Chimica Acta, 2024)

Arsenic field test kits based on solid-phase fluorescence filter effect induced by silver nanoparticle formation - Wenhui Yang; Liqing Ye; Yuke Wu; Xi Wang; Simin Ye; Yurong Deng; Ke Huang; Hong Luo; Jinyi Zhang; Chengbin Zheng (Journal of Hazardous Materials, 2024)

Particle coating growth behaviors in a spray fluidized bed based on Gas-Liquid-Solid Quasi-Three-phase DEM numerical simulation - Aiming Deng; Tianqi Tang; Shanshan Sun; Yurong He (Chemical Engineering Journal, 2023)

Paper-assisted ratiometric fluorescent sensors for on-site sensing of sulfide based on the target-induced inner filter effect - Yao Lin; Simin Ye; Jinxiao Tian; Anqin Leng; Yurong Deng; Jinyi Zhang; Chengbin Zheng (Journal of Hazardous Materials, 2023)

Bacterial diversity and its correlation with sensory quality of two types of zha-chili from Shennongjia region, China - Zhendong Zhang; Huijun Zhao; Yumei Deng; Wen Luo; Xiyun Luo; Chan Wang; Changbin Quan; Zhuang Guo; Yurong Wang (Food Research International, 2023)

A high-throughput atomic emission analyzer for simultaneous field detection of dissolved inorganic and organic carbon in seawater and lake water - Yubin Su; Yao Lin; Yuanyuan Li; Tian Ren; Yurong Deng; Chengbin Zheng (Analytica Chimica Acta, 2023)

Accumulation, transportation, and distribution of tetracycline and cadmium in rice - Chunfeng He; Jini Zhou; Chen Yang; Zhiyi Song; Junheng He; Ziqing Huang; Yurong Deng; Jinling Wang; Yu Xiong; Zhi Dang (Journal of Environmental Sciences, 2023)

miR-146a-3p suppressed the differentiation of hAMSCs into Schwann cells via inhibiting the expression of ERBB2 - Wei Chen; Linlin Ji; Zairong Wei; Chenglan Yang; Shusen Chang; Yucheng Zhang; Kaiyu Nie; Lingli Jiang; Yurong Deng (Cell and Tissue Research, 2021)
Human amniotic mesenchymal stem cells (hAMSCs) can be differentiated into Schwann-cell-like cells (SCLCs) in vitro. However, the underlying mechanism of cell differentiation remains unclear. In this study, we explored the phenotype and multipotency of hAMSCs, which were differentiated into SCLCs, and the expression of nerve repair-related Schwann markers, such as S100 calcium binding protein B (S-100), TNF receptor superfamily member 1B (P75), and glial fibrillary acidic protein (GFAP) were observed to be significantly increased. The secreted functional neurotrophic factors, like brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), and neurotrophin-3 (NT-3), were determined and also increased with the differentiation time. Moreover, miR-146a-3p, which significantly decreased during the differentiation of hAMSCs into SCLCs, was selected by miRNA-sequence analysis. Further molecular mechanism studies showed that Erb-B2 receptor tyrosine kinase 2 (ERBB2) was an effective target of miR-146a-3p and that miR-146a-3p down-regulated ERBB2 expression by binding to the 3′-UTR of ERBB2. The expression of miR-146a-3p markedly decreased, while the mRNA levels of ERBB2 increased with the differentiation time. The results showed that down-regulating miR-146a-3p could promote SC lineage differentiation and suggested that miR-146a-3p negatively regulated the Schwann-like phenotype differentiation of hAMSCs by targeting ERBB2. The results will be helpful to establish a deeper understanding of the underlying mechanisms and find novel strategies for cell therapy.